2011
DOI: 10.1182/blood-2010-08-304477
|View full text |Cite
|
Sign up to set email alerts
|

Cancerous inhibitor of PP2A (CIP2A) at diagnosis of chronic myeloid leukemia is a critical determinant of disease progression

Abstract: Prospective identification of patients whose chronic myeloid leukemia (CML) will progress to blast crisis is currently not possible. PP2A is a phosphatase and tumor suppressor that regulates cell proliferation, differentiation, and survival. Cancerous inhibitor of PP2A (CIP2A) is a recently described inhibitor of PP2A in breast and gastric cancer. The aim of this study was to investigate whether CIP2A played a role in CML and whether PP2A or its inhibitor proteins CIP2A or SET could predict clinical outcome. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
123
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(130 citation statements)
references
References 32 publications
(62 reference statements)
7
123
0
Order By: Relevance
“…9 In AML cell lines and primary cells, 10058-F4 has been shown to inhibit growth, induce cell cycle arrest and cause differentiation.…”
Section: A B C D E F Gmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In AML cell lines and primary cells, 10058-F4 has been shown to inhibit growth, induce cell cycle arrest and cause differentiation.…”
Section: A B C D E F Gmentioning
confidence: 99%
“…6,7 Many malignancies, including CML, are associated with inhibition of protein phosphatase 2A (PP2A). 8,9 A novel protein inhibitor of PP2A, cancerous inhibitor of PP2A (CIP2A, KIAA1525) is associated with poor outcome in many malignancies. In CML, CIP2A protein level at chronic phase diagnosis is a prospective biomarker of disease progression in imatinib-treated CML patients.…”
mentioning
confidence: 99%
“…CIP2A is a widespread oncogenic factor in human neoplasms (4)(5)(6)(7)(8)(9)3). Similar to the Ras oncogene, CIP2A is required for anchorage-independent cell growth and malignant transformation of human cells (4).…”
Section: A B C Discussionmentioning
confidence: 99%
“…Previous studies have shown that CIP2A serves a critical role in the progression of several cancer types, including head and neck squamous cell carcinoma, oral squamous cell carcinoma, oesophageal squamous cell carcinoma, colon, gastric, breast, prostate, tongue, lung, cervical cancer and acute myeloid leukaemia (3)(4)(5)(6)(7)(8)(9). In 2009, CĂ´me et al (10) demonstrated that CIP2A is associated with clinical aggressivity in human breast cancer and promotes the malignant growth of breast cancer cells (10).…”
Section: Introductionmentioning
confidence: 99%
“…At a high dose, MCs cause massive changes in cell morphology through cytoskeletal rearrangements and oxidative stress, leading to loss of cell-to-cell adhesion and cell death [175][176][177]. In a chronic model of low level exposure, constant mild PP2A inhibition leads to reprogramming of the cell, runaway cell growth, and tumor production, analogous to the effects of endogenous human protein CIP2A (cancerous inhibitor of PP2A) associated with breast and lung cancer [178][179][180][181].…”
Section: Effects On Other Tissues From Oral Exposure To Mcsmentioning
confidence: 99%